MODEL SISTEM PERADILAN ANAK DENGAN PENDEKATAN PSIKOLEGAL - Panji Asmara, Gregorius Yoga; Mangesti, Yovita Arie (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Child protection is a constitutional right to realize human rights even though it is aimed at child offenders. The problem of saving culture (deviant culture) is still a major consideration as a cause of the emergence of bad behavior by children. Psycholegal approach found that crime committed by children is influenced by the process of imitation. Incorrect socialization in this imitation process, or exposure to violations of the law, is obtained from the family or social environment around children during prenatal, Christmas, adolesencence until adulthood. Starting from the wrong socialization process and the inability to understand the law in childhood. become one of the triggers of crime. The juvenile justice system model with a psycholegal approach requires diversion by strengthening the legal substance, namely (a) right to as soon as possible without delay by a free/impartial judiciary, (b) standardization of parents/supervisors who are monitored, (c) revitalization of roles Bapas as the oversight body diversion. (d) the elimination of stigmatization and (e) respect for children's privacy rights.Perlindungan anak merupakan hak konstitusional untuk mewujudkan hak asasi manusia meskipun itu ditujukan bagi anak pelaku kejahatan. Masalah sub-budaya menyimpan (deviant culture) masih menjadi pertimbangan utama sebagai penyebab munculnya perilaku jahat oleh anak. Pendekatan psikolegal menemukan bahwa kejahatan yang dilakukan anak dipengaruhi proses peniruan. Sosialisasi yang salah pada proses peniruan ini, atau terpaparnya tindak pelanggaran hukum, didapat dari keluarga atau lingkungan sosial di sekitar anak semasa prenatal, natal, adolesencence hingga dewasa.. Bertitik tolak dari proses sosialisasi yang salah serta ketidakmampuan memahami hukum di masa kanak-kanak ini menjadi salah satu pemicu munculnya kejahatan. Model sistem peradilan anak dengan pendekatan psikolegal menghendaki diversi dengan penguatan substansi hukum, yaitu (a) hak untuk sesegera mungkin tanpa penundaan oleh badan pengadilan yang bebas/tidak memihak, (b) standarisasi orang tua/pengampu yang terpantau, (c) revitalisasi peran Bapas sebagai badan pengawas diversi. (d) penghapusan stigmasi dan (e) penghargaan terhadap hak privasi anak.